Diagenetic silica enrichment and late‐stage groundwater activity in Gale crater, Mars. Issue 10 (30th May 2017) - Frydenvang, J.; Gasda, P. J.; Hurowitz, J. A.; Grotzinger, J. P.; Wiens, R. C.; Newsom, H. E.; Edgett, K. S.; Watkins, J.; Bridges, J. C.; Maurice, S.; Fisk, M. R.; Johnson, J. R.; et al.
Abstract: Diagenetic silica enrichment in fracture‐associated halos that crosscut lacustrine and unconformably overlying aeolian sedimentary bedrock is observed on the lower north slope of Aeolis Mons in Gale crater, Mars. The diagenetic silica enrichment is colocated with detrital silica enrichment observed in the lacustrine bedrock yet extends into a considerably younger, unconformably draping aeolian sandstone, implying that diagenetic silica enrichment postdates the detrital silica enrichment. A causal connection between the detrital and diagenetic silica enrichment implies that water was present in the subsurface of Gale crater long after deposition of the lacustrine sediments and that it mobilized detrital amorphous silica and precipitated it along fractures in the overlying bedrock. Although absolute timing is uncertain, the observed diagenesis likely represents some of the most recent groundwater activity in Gale crater and suggests that the timescale of potential habitability extended considerably beyond the time that the lacustrine sediments of Aeolis Mons were deposited. Key Points: Silica‐rich diagenetic halos penetrate lacustrine and unconformably draping aeolian bedrock in Gale crater, Mars Colocation of diagenetic and detrital silica suggests aqueous remobilization of detrital silica Presence of diagenetic halos in the unconformably draping aeolian bedrock suggests late‐stage groundwater activity in Gale crater